1997
DOI: 10.1039/a606244j
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced electron transfer from tetraethoxyethene to C60 and C70 studied by laser flash photolysis

Abstract: The electron transfer from tetraethoxyethene (TEOE), which has high electron-donor ability, to photoexcited C 60 or C 70 in polar and less polar solvents has been investigated by 532 nm laser flash photolysis with observation of the transient absorption bands in the near-IR region. The transient absorption bands of the triplet states of fullerenes ( T C 60 * and T C 70 *), which appeared immediately after nanosecond laser exposure, were effectively quenched by TEOE. With the decay of T C 60 * and T C 70 *, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…It is now well-known that the triplet excited state of C 60 is formed by efficient intersystem crossing. , The triplet excited state of C 60 has a reduction potential of E 0 red = 1.14 V versus SCE and can therefore be reduced by a variety of organic compounds giving the C 60 radical anion. ,, A long-lived transient of C 60 •- has been reported to be formed in photoinduced electron transfer from ZnO or TiO 2 semiconductor colloids to C 60 . In homogeneous systems, however, the lifetime of the generated C 60 •- is generally extremely short as a result of fast back electron transfer to the reactant pair, resulting in no net formation of C 60 •- . , We report herein that the photoinduced electron transfer from an NADH analogue, 1-benzyl-1,4-dihydronicotinamide (BNAH), and the dimer analogue [(BNA) 2 ] to the triplet excited state of C 60 ( 3 C 60 *) yields stable C 60 •- in benzonitrile solution with a surprisingly high quantum yield, exceeding unity in the latter case; Φ = 1.3. We also report the selective two-electron reduction of C 60 to the tert -butylated C 60 anion ( t -BuC 60 - ) and 1,2-dihydro[C 60 ]fullerene (1,2-C 60 H 2 ) via photoinduced electron transfer from 4- tert -butyl-1-benzyl-1,4-dihydronicotinamide ( t -BuBNAH) and 10-methyl-9,10-dihydroacridine (AcrH 2 ) to 3 C 60 *, respectively …”
Section: Introductionmentioning
confidence: 99%
“…It is now well-known that the triplet excited state of C 60 is formed by efficient intersystem crossing. , The triplet excited state of C 60 has a reduction potential of E 0 red = 1.14 V versus SCE and can therefore be reduced by a variety of organic compounds giving the C 60 radical anion. ,, A long-lived transient of C 60 •- has been reported to be formed in photoinduced electron transfer from ZnO or TiO 2 semiconductor colloids to C 60 . In homogeneous systems, however, the lifetime of the generated C 60 •- is generally extremely short as a result of fast back electron transfer to the reactant pair, resulting in no net formation of C 60 •- . , We report herein that the photoinduced electron transfer from an NADH analogue, 1-benzyl-1,4-dihydronicotinamide (BNAH), and the dimer analogue [(BNA) 2 ] to the triplet excited state of C 60 ( 3 C 60 *) yields stable C 60 •- in benzonitrile solution with a surprisingly high quantum yield, exceeding unity in the latter case; Φ = 1.3. We also report the selective two-electron reduction of C 60 to the tert -butylated C 60 anion ( t -BuC 60 - ) and 1,2-dihydro[C 60 ]fullerene (1,2-C 60 H 2 ) via photoinduced electron transfer from 4- tert -butyl-1-benzyl-1,4-dihydronicotinamide ( t -BuBNAH) and 10-methyl-9,10-dihydroacridine (AcrH 2 ) to 3 C 60 *, respectively …”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes such as C 60 and C 70 were known to accelerate the photoinduced electric conductivity when they are added into some molecules such as phthalocyanines and porphyrins. In solutions and polymer films, the mechanisms of the photoinduced electron-transfer reactions of fullerenes have been investigated by photochemical techniques such as laser flash photolysis. In the mixture system of C 60 (or C 70 ) with electron donors in polar solvents, C 60 •- and C 70 •- were usually produced via their triplet states ( T C 60 * and T C 70 *) which abstract the electron from the electron donors such as aromatic amines when the concentrations of electron donors are appropriately dilute. For the C 60 compounds connected with chromophores by the covalent bonds, photoinduced electron transfer takes place via the singlet state of the chromophores. …”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of photochemistry, C 60 and C 70 are good electron acceptors and many photoinduced reactions have been reported by using these fullerenes as acceptors . For example, generations of adducts of C 60 have been observed in laser photolysis studies with anthracene 4a and with tetraethoxyethene 4b. It is also reported that doping of fullerenes to polymer films such as polyvinylcarbazole and poly( p -phenylene vinylene) results in the enhancement of photoconductivity …”
Section: Introductionmentioning
confidence: 99%